2014
DOI: 10.3386/w20268
|View full text |Cite
|
Sign up to set email alerts
|

Learning Millennial-Style

Abstract: The growing use of on-line educational content and related video services has changed the way people access education, share knowledge, and possibly make life decisions. In this paper, we characterize how video content affects individual decision-making and willingness to share in the context of a personal financial decision. Content geared toward giving better instructions leads to better financial decisions, but less information sharing. Misleading advertising not only causes worse decisions, but makes it le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The experimental approach oers important advantages in settings where naturalistic interventions are highly composite and heterogeneous. Programmatic diversity may help to explain why dierent authors have reached dierent conclusions concerning the behavioral eects of nancial education; see, for example, Duo and Saez (2003), Bayer et al (2009), Bayer, Bernheim andScholz (2009), Goda, Manchester and Sojourner (2012), Cole and Shastry (2012), Cole, Sampson and Zia (2011), Skimmyhorn (2012), Servon and Kaestner (2008), Collins (2010), Lührmann, Serra-Garcia andWinter (2014), Mandell (2009), Bertrand andMorse (2011), Drexler, Fischer andSchoar (2014), Carlin, Jiang and Spiller (2014), Heinberg et al (2014), Lusardi et al (2014), andBrown et al (2014), as well as the chapter on personal nancial decision making in this volume, Beshears et al (forthcoming). Recent surveys by Hastings, Madrian and Skimmyhorn (2013) and Lusardi and Mitchell (2014a) underscore the mixed nature of the available empirical evidence.…”
Section: The Behavioral Eects Of Nancial Educationmentioning
confidence: 99%
“…The experimental approach oers important advantages in settings where naturalistic interventions are highly composite and heterogeneous. Programmatic diversity may help to explain why dierent authors have reached dierent conclusions concerning the behavioral eects of nancial education; see, for example, Duo and Saez (2003), Bayer et al (2009), Bayer, Bernheim andScholz (2009), Goda, Manchester and Sojourner (2012), Cole and Shastry (2012), Cole, Sampson and Zia (2011), Skimmyhorn (2012), Servon and Kaestner (2008), Collins (2010), Lührmann, Serra-Garcia andWinter (2014), Mandell (2009), Bertrand andMorse (2011), Drexler, Fischer andSchoar (2014), Carlin, Jiang and Spiller (2014), Heinberg et al (2014), Lusardi et al (2014), andBrown et al (2014), as well as the chapter on personal nancial decision making in this volume, Beshears et al (forthcoming). Recent surveys by Hastings, Madrian and Skimmyhorn (2013) and Lusardi and Mitchell (2014a) underscore the mixed nature of the available empirical evidence.…”
Section: The Behavioral Eects Of Nancial Educationmentioning
confidence: 99%
“…Consistent with our findings, recent work by Brown et al (2014) shows that the effects of high school financial education on behavior are most pronounced when schools offer full courses taught by trained teachers. More generally, the considerations highlighted in the current study may help to explain why different authors reach different conclusions about the effects of financial education when studying different programs; see in particular Duflo and Saez (2003), Bayer, Bernheim and Scholz (2009), Goda, Manchester and Sojourner (2014), Cole and Shastry (2010), Cole, Sampson and Zia (2011), Skimmyhorn (2012), Servon and Kaestner (2008), Collins (2013), Lührmann, Serra- Garcia and Winter (2015a), Mandell (2009), Drexler, Fischer and Schoar (2014), Carlin, Jiang and Spiller (2014), Heinberg et al (2014), Lusardi et al (2015), and Bertrand and Morse (2011).…”
Section: Introductionmentioning
confidence: 80%
“…, as well as five questions about the material covered in the video shown to the control group. 30Previous studies have also examined self-reported decision strategies (for instanceHeinberg et al, 2014; Lührmann, Serra-Garcia and Winter, 2015b;Carlin, Jiang and Spiller, 2014). In the final stage Future Reward r Investment Amount a Daily Interest Rate R Number of Doublings…”
mentioning
confidence: 99%
“…For a review of structural behavioral economics, see DellaVigna (2018). 5 While there is a substantial literature on the effects of financial education, most of it focuses on measuring changes in behavior rather than on the quality of decision making; see(Duflo and Saez, 2003;Bayer et al, 2009;Mandell, 2009;Cole and Shastry, 2010;Bertrand and Morse, 2011;Cole et al, 2011;Skimmyhorn, 2012Skimmyhorn, , 2016Servon and Kaestner, 2008;Collins, 2013;Drexler et al, 2014;Carlin et al, 2014;Heinberg et al, 2014;Goda et al, 2014;Luhrmann et al, 2018;Lusardi et al, 2015;Song, 2015;Bruhn et al, 2016;Urban et al, 2018;Sutter et al, 2020). Exceptions primarily include studies, discussed below, that evaluate financial literacy or draw inferences about decision quality from directional effects on behavior.…”
mentioning
confidence: 99%